Reducing Wild Meat Sales and Promoting Local Food Security: Lessons Learnt from a Behavior Change Campaign in Yangambi, Democratic Republic of Congo - van Vliet, Nathalie; Gonzalez, Ahtziri; Nyumu, Jonas; Muhindo, Jonas; Paemelaere, Evi; Cerutti, Paolo; Nasi, Robert (Ethnobiology and Conservation, 2022)
Marketing strategies to promote behavioral change are increasingly used to reduce the unsustainable use of wild meat. One of the mayor keys for success of behavior change campaigns lies in the choice of the channel for communication and the messaging. In this research, we present a behavioral change campaign implemented in Yangambi, Democratic Republic of Congo framed around an integrated conservation and development objective: improve food security in rural communities, reduce the unsustainable use of wildlife for food and promote locally grown pork and chicken. The campaign was co-developed based on the research team’s knowledge of the hunting system in the study area and the participation of key local stakeholders (village leaders, hunters and their families). It used participatory community theater, various printed materials, radio and face to face interactions. We evaluated the efficiency and clarity of messaging for channels used through semi-structured interviews with hunters, households and wildlife traders. We found that participatory community theater resulted in increased clarity and understanding among hunters and households. Moreover, community theater promoted word-of-mouth communication that reached an audience well beyond the location where the theater was held. Messages that were framed positively and used amusing channels of communication triggered positive receptiveness by our audience. Using local languages, avoiding written materials for illiterate audiences, and using repetitive means of communication may be among the strategies that could help increase the clarity of communication messages, particularly for sensitive topics such as this one. Our work calls for more lessons learnt from the ground about the most appropriate communication channels and messages, keeping in mind the social and cultural background of the audience, and ensuring that messages trigger emotions that lead to the desired changes.